2011
DOI: 10.1007/s11199-011-9936-1
|View full text |Cite
|
Sign up to set email alerts
|

College Women’s Feminist Identity: A Multidimensional Analysis with Implications for Coping with Sexism

Abstract: This study examined components of women’s feminist identity and possible relations to their reported coping responses to sexism. A sample of 169 undergraduate women (M = 19.4 y, SD = 1.2) from diverse ethnic backgrounds completed surveys assessing their experiences and gender-related views. The first set of analyses revealed that women’s social gender identity, exposure to feminism, and gender-egalitarian attitudes independently contributed to feminist identification; moreover, non-stereotyping of feminists fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 71 publications
4
62
0
4
Order By: Relevance
“…Prior studies have found that feminist identity may be related to recognizing and labeling sexist events (Kobrynowicz & Branscombe, 1997;Moradi & Subich, 2002) and engaging in collective action (Duncan, 1999(Duncan, , 2010Liss, Crawford, & Popp, 2004;Nelson et al, 2008;Yoder, Tobias, & Snell, 2011;Zucker, 2004). Furthermore, feminists point to their own experiences with gender discrimination as contributors to their feminist identity development (Klonis, Endo, Crosby, & Worell, 1997;Zucker, 2004), endorse confronting sexist acts (Leaper & Arias, 2011), and report that they have personally taken measures to confront sexism (Ayres, Friedman, & Leaper, 2009;Zucker, 2004).…”
Section: The Feminist Stigmamentioning
confidence: 99%
“…Prior studies have found that feminist identity may be related to recognizing and labeling sexist events (Kobrynowicz & Branscombe, 1997;Moradi & Subich, 2002) and engaging in collective action (Duncan, 1999(Duncan, , 2010Liss, Crawford, & Popp, 2004;Nelson et al, 2008;Yoder, Tobias, & Snell, 2011;Zucker, 2004). Furthermore, feminists point to their own experiences with gender discrimination as contributors to their feminist identity development (Klonis, Endo, Crosby, & Worell, 1997;Zucker, 2004), endorse confronting sexist acts (Leaper & Arias, 2011), and report that they have personally taken measures to confront sexism (Ayres, Friedman, & Leaper, 2009;Zucker, 2004).…”
Section: The Feminist Stigmamentioning
confidence: 99%
“…Relevant research is more limited on feminist identity or beliefs in relation to coping responses to sexism. Two relevant studies of undergraduate women found that feminist self‐identification increased the likelihood that women positively appraised confronting sexist acts (Leaper & Arias, ) or reported previously confronting an actual sexist event (Ayres et al., ). Thus, to the extent that sexist acts violate their values, we hypothesized that girls with a feminist identity would be more likely to seek redress of the injustice through approach coping.…”
Section: Possible Assets and Risks Related To Girls’ Cognitive Appraimentioning
confidence: 99%
“…First, education and its outcomes may give women access to material resources in the form of finances, authority, and social networks that enable them to actively respond to discriminatory experiences [3638]. Second, education may act directly by establishing a historical context for discrimination, connecting women with a wider feminist movement, and giving women the knowledge to access resources to respond to discriminatory experiences [39, 40]. Third, education may affect health behaviors such as drug use in response to stress through psychosocial factors.…”
Section: Introductionmentioning
confidence: 99%